Poly(N-isopropylacrylamide-co-N-vinylpyrrolidone) thermoresponsive microspheres: The low drug loading ensures the pulsatile release mechanism - G. Fundueanu; M. Constantin; S. Bucatariu; P. Ascenzi (eXPRESS Polymer Letters, 2020)
Poly(N-isopropylacrylamide-co-N-vinylpyrrolidone) (poly(NIPAAm-co-NVP)) with a co-monomer molar ratio in copolymer of 91.5/8.5 (NIPAAm/NVP) was synthesized as an interesting thermosensitive material possessing a sharp phase transition at 36 °C under simulated physiological conditions. The effect of the co-monomer molar ratio as well as of the ionic strength and nature of ions on the lower critical solution temperature (LCST) was investigated. Cross-linked poly(NIPAAm-co-NVP) thermoresponsive microspheres were synthesized by the suspension polymerization technique respecting the same NIPAAm/NVP molar ratio as for linear polymer. The microspheres were loaded with the model drug diclofenac (DF) by the solvent evaporation method; differential scanning calorimetry (DSC) demonstrates a dispersion of drug crystals within the polymeric matrix. The DF release rate is deeply influenced by the drug loading degree. Only microspheres with low DF loading are able to release the bioactive compound through a pulsatile mechanism.